CENTRAL ASIA: REGIONAL RESPONSE TO A GLOBAL CHALLENGE - TOLIPOV, Farkhad (CENTRAL ASIA AND THE CAUCASUS, 2009)
Central Asia should take up the challenge of globalization, hence the question: How should the Central Asian countries respond to it and what constitutes the challenge after all? Globalization means that all sorts of international factors (economic, political, cultural, information exchange, etc.) have come to play an ever-increasing role in the social sphere of various countries. To a certain extent this can be described as a “global challenge to Central Asia.” Independence and sovereignty issues are two additional factors of the global challenge—this cannot be doubted or disputed. The new geopolitical Great Game has reached its culmination: indeed, the struggle for independence of the former Soviet republics did not end in 1991. It reached new heights in the early 21st century. Throughout the period of their technical rather than real independence, the Central Asian countries were living, developing, and building their statehoods under permanent geopolitical stress. They failed to coordinate their foreign policies, thus burying the course toward integration formulated in December 1991 as a response to the Soviet Union’s disintegration. There is another, no less important, aspect related to the essence of the budding world order and the countries’ attitude to it. The Central Asian countries, like all the other post-Soviet states, were carried away by the fictitious concept of the multi-polar world (an antinomy of the unipolar world theory) softly imposed on them. The present system of international relations has two most important aspects identified from the position of world order as a “regionalized and multi-sided world.” Regionalized should be interpreted as the world’s geographic regulation while “multi-sided” (but not multi-polar) describes entity regulation. At all times world order has been related to the problem of territorial control and the means and methods of administering it the controlling entities selected. During the Cold War period it was not the regionalization principle that was at play but rather the division into spheres of influence between the two powers. The resultant world order could be described as bipolar. Today, the spheres of influence are replaced with regions while the entities of world order can no longer be described as poles, but rather as various sides involved states and international organizations. This means that the Central Asian countries should abandon the principles of the multi-polar world policies for the sake of regionalized and multi-sided relations.